Extreme oncoplastic breast surgery: A case report. (2016) - Bordoni, Daniele; Cadenelli, Pierfrancesco; Falco, Giuseppe; Rocco, Nicola; Manna, Paola; Tessone, Ariel; Ornelli, Matteo; Magalotti, Cesare
Highlights: Many oncoplastic approaches have been proposed for breast cancer surgery but few have been described for multicentric cancers. "Extreme oncoplastic surgery" allows successful breast conservation in selected patients with multicentric tumors. We present an application of oncoplastic breast surgery in a case of multicentric breast cancer with optimal outcomes. Abstract: Introduction: So called "extreme oncoplastic surgery" is emerging as a new promising concept in breast cancer surgery allowing successful breast conservation in selected patients with multicentric tumors. Presentation of case: We report the case of a 48-year-old woman presenting with a multicentric breast cancer and successfully treated with an oncoplastic technique consisting in three radical lumpectomies followed by breast reshaping and simultaneous contralateral symmetrization. Discussion: According to our experience, oncoplastic conserving breast surgery could represent a better option than the combination of mastectomy, reconstruction and radiation therapy, in terms of quality of life for selected patients affected by multicentric breast cancer. Conclusion: The surgical treatment for multicentric breast cancers remains controversial even though emerging evidences show good oncological and aesthetic outcomes following oncoplastic conserving breast surgery.